Isolated dislocation of a supplementary sulcus pseudophakic intraocular lens. Issue 6 (June 2015) - O'Brart, David P.S.; Hirji, Nashila
Abstract : N/A: We report the case of a woman with pseudoexfoliation who presented with a hyperopic refractive surprise and uncontrolled intraocular pressure (IOP) following cataract surgery and in‐the‐bag intraocular lens (IOL) implantation in the left eye. Trabeculectomy was performed, and a supplementary (piggyback) sulcus IOL was inserted. At 5 years, the uncorrected distance visual acuity (UDVA) was 20/16 and the IOP was less than 21 mm Hg. Following head trauma, the patient experienced blurred vision. The UDVA was 20/125, correcting to 20/25 with +3.00 −0.75 × 105. The IOL in the capsular bag was not dislocated, but the sulcus IOL was not in the posterior chamber; it was found by ultrasound in the temporal anterior vitreous gel. At‐risk patients having supplementary IOL insertion should be warned of this possible late problem. Financial Disclosure : Neither author has a financial or proprietary interest in any material or method mentioned.